Upgrading Educational Quality through Synergy of Teaching and Research - Erdyneeva, Klavdiya G.; Nikolaev, Evgeni L.; Azanova, Albina A.; Nurullina, Guzel N.; Bogdanova, Venera I.; Shaikhlislamov, Albert K.; Lebedeva, Inessa V.; Khairullina, Elmira R. (International Review of Management and Marketing, 2016)
This paper is a part of an ongoing attempt to reflect on the ways and results related to developing research competence, which is considered as an urgent issue for contemporary higher education in Russia. The polypragmatic approach, the major approach used to study the issue, is an integrity of dialectic, exploratory, synergetic and competence approaches that ensures success and effectiveness in developing student research competence. The new approach in considering the competence paradigm in teaching Humanities is associated with predomination of the synergetic principles aimed at developing their intellectual level, high-tech skills, and skills useful in making appropriate decisions in situations requiring high level of a person’s inner organization, deep understanding of concepts, and ability to convert the knowledge into competencies. The authors try to prove that to effectively apply the best practice, humanitarians, as professionals, must understand the basis and synergy of research. In this regard, research skills have been looked upon as a part of a curriculum redevelopment process that still needs enhancement. The authors consider Humanities student attitudes towards research with regard to their ability to use theoretical and methodological basis needed to form their research competence, and come to a conclusion that the approach implemented have improved student self-perceived competence in conducting a research project. They also share their opinions and findings on the structure and synergy of developing self-efficacy in self-organization and self-transformation when carrying out a research project. The information and findings may be useful for practitioners in humanitarian higher education institutions, as well as for further development and contribution into the process of upgrading the system of higher education in Russia. Keywords: research competence, synergetic approach, interdisciplinary approach, self-organization, self-transformation, innovation, teaching Humanities. JEL Classifications: A23, I23, I26